If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) = 63 Reorder the terms: 3(-7 + x) = 63 (-7 * 3 + x * 3) = 63 (-21 + 3x) = 63 Solving -21 + 3x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 3x = 63 + 21 Combine like terms: -21 + 21 = 0 0 + 3x = 63 + 21 3x = 63 + 21 Combine like terms: 63 + 21 = 84 3x = 84 Divide each side by '3'. x = 28 Simplifying x = 28
| Ln(x)=-90 | | 3(c-4)=3c-12 | | -6p+8+7p=12 | | 7r^2+10r-72=0 | | 2w=36+5w | | 7r^2+10-72=0 | | 3y+15x=-24 | | 100+10xlog=60 | | 3x-3x-4=4 | | 2t-S=2u | | 6y-48=8 | | 4x=-2x-8 | | -9-4(-11)= | | -11x+4=62 | | 2ln(x+1)=ln(x^2-1) | | 3y-7y=-3y+-19 | | 3x^2-33y=0 | | 3x+20+3y=180 | | 11sin(x)+5=sin(x) | | N+0=3.478 | | 55.99+80= | | 16(x-8)= | | 70+60+8x+2=360 | | 2(w+6)=-2(5w-5)+8w | | y-5=-7(x+6) | | 3=19.99x | | f(x)=8x^3+5 | | 2x+15+x+15=360 | | 5(4+2x)-1(8x-12)=69 | | 15x-7=1.5x+87.5 | | -46-12x=-8x+46 | | 6m+3m=6m-9 |